A rotational investigation of the three isomeric forms of cyanoethynylbenzene (HCC-C6H4-CN): benchmarking experiments and calculations using the "Lego brick" approach. Issue 8 (13th February 2023) - Spaniol, Jean-Thibaut; Lee, Kin Long Kelvin; Pirali, Olivier; Puzzarini, Cristina; Martin-Drumel, Marie-Aline
Abstract : Benchmarking experiments and calculations using the "Lego brick" approach on cyanoethynylbenzene isomers. Abstract : We report the study of three structural isomers of phenylpropiolonitrile (3-phenyl-2-propynenitrile, C6 H5 –C3 N) containing an alkyne function and a cyano group, namely ortho -, meta -, and para -cyanoethynylbenzene (HCC–C6 H4 –CN). The pure rotational spectra of these species have been recorded at room temperature in the millimeter-wave domain using a chirped-pulse spectrometer (75–110 GHz) and a source-frequency modulation spectrometer (140–220 GHz). Assignments of transitions in the vibrational ground state and several vibrationally excited states were supported by quantum chemical calculations using the so-called "Lego brick" approach [A. Melli, F. Tonolo, V. Barone and C. Puzzarini, J. Phys. Chem. A, 2021, 125, 9904–9916]. From these assignments, accurate spectroscopic (rotational and centrifugal distortion) constants have been derived: for all species and all observed vibrational states, predicted rotational constants show relative accuracy better than 0.1%, and often of the order of 0.01%, compared to the experimental values. The present work hence further validates the use of the "Lego brick" approach for predicting spectroscopic constants with high precision.